Effect of over-the-counter fluoridated products regimens on root caries inhibition. Issue 10 (October 2015) - Arthur, Rodrigo Alex; Martins, Vanessa Balbé; de Oliveira, Caroline Longaray; Leitune, Vicente Castelo Branco; Collares, Fabrício Mezzomo; Magalhães, Ana Carolina; Maltz, Marisa
Highlights The prevalence of root caries is increasing mainly in elderly. There is no consensus on non-invasive treatment for this disease. Dentine carious lesions were exposed to over-the-counter fluoridated products. Dentifrice thrice a day has better caries inhibition than associated with mouthwash. Dentifrice thrice a day has better caries inhibition than its use twice a day.